1980
DOI: 10.7589/0090-3558-16.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Wasting Disease of Captive Mule Deer: A Spongiform Encephalopathy

Abstract: In the past 12 years (1967-79) a syndrome we identify as chronic wasting disease has been observed in 53 mule deer (Odocoileus hemionus hemionus) and one black-tailed deer (Odocoileus hemionus columbianus) held in captivity in several wildlife facilities in Colorado and more recently in Wyoming. Clinical signs were seen in adult deer and included behavioral alterations, progressive weight loss and death in 2 weeks to 8 months. Gross necropsy findings included emaciation and excess rumen fluid admixed with sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
505
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(521 citation statements)
references
References 3 publications
5
505
0
4
Order By: Relevance
“…Therefore, the capacity for CWD to cross species barriers has been of great interest. Until recently, natural CWD infections were believed to infect only white-tailed deer, mule deer, and Rocky Mountain elk [89,90,92]. This ended in 2006, when a report indicated that Shira's moose could be orally-infected with brain homogenate from CWD-infected mule deer, and shortly thereafter a natural case of a CWD-infected moose was discovered [4,42].…”
Section: Natural Cwd Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the capacity for CWD to cross species barriers has been of great interest. Until recently, natural CWD infections were believed to infect only white-tailed deer, mule deer, and Rocky Mountain elk [89,90,92]. This ended in 2006, when a report indicated that Shira's moose could be orally-infected with brain homogenate from CWD-infected mule deer, and shortly thereafter a natural case of a CWD-infected moose was discovered [4,42].…”
Section: Natural Cwd Infectionsmentioning
confidence: 99%
“…Only one study has been performed on cervid susceptibility to sheep scrapie by the ic route, and showed that 3 of 6 elk developed neurologic signs, spongiform encephalopathy and PrP Sc in brain [25]. Further experiments to address this question may be interesting since sheep scrapie is considered a possible source for CWD in North America [89,91].…”
Section: Interspecies Cwd Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…CWD was first detected in cervids in the late 1960s in Colorado [2,3] and has since spread to an increasing number of other US states and Canadian provinces [4,5]. The disease is transmitted horizontally by contact with pathogenic prions shed in bodily fluids [6,7] and vertically from mother to offspring [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…and wapiti (Cervus elaphus nelsoni), has emerged as an important wildlife health problem in several parts of North America Williams et al, 2002). Epidemics of CWD appear to be self-sustaining, with transmission likely occurring in both the presence and absence of live, infected animals and infectious agents persisting in contaminated environments (Williams and Young, 1992;Miller et al, 1998Miller et al, , 2000Miller et al, , 2004Williams and Miller, 2002;Miller and Williams, 2003;Miller and Wild, 2004).…”
Section: Introductionmentioning
confidence: 99%